Management of anticoagulation in patients with prosthetic heart valves undergoing oral and maxillofacial operations - K. Webster,* J. Wilde (Blackwell Synergy, 2000)
It is estimated that over 300 000 people in the UK are taking oral anticoagulants, and many of them are doing so to prevent thromboembolism from mechanical heart valves. The type and position of the prosthetic valve influence the risk of thromboembolism, and thromboembolic events occur more frequently with mitral than with aortic valves, and in people with co-existing atrial fibrillation (AF).